A high-heat-conducting-efficiency, high-temperature-resistant composite material, preparation process and application thereof

By mixing the inorganic adhesive obtained by mixing phosphoric acid, aluminum hydroxide, zinc oxide and magnesium oxide with composite ceramic powder and spraying it on an aluminum substrate, the problem of the non-stick coating of the rice cooker's inner liner is solved, and the durability, thermal conductivity and high-temperature resistance of high-temperature composite materials are improved.

CN118852897BActive Publication Date: 2025-03-14GUANGDONG CHUANGSHENG STAINLESS STEEL PROD CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410825866.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-06-25
Publication Date
2025-03-14
Estimated Expiration
2044-06-25

AI Technical Summary

Technical Problem

The non-stick coating of the existing rice cooker can easily fall off, resulting in health and safety threats such as sticking pots and pans, and lack of durability.

Method used

The inorganic adhesive obtained by mixing phosphoric acid, aluminum hydroxide, zinc oxide and magnesium oxide is mixed with the composite ceramic powder and sprayed on the aluminum matrix to form a high-thermal conductivity and high-temperature resistant composite material.

Benefits of technology

The durability, thermal conductivity and high temperature resistance of high-temperature composite materials are improved, and the risk of adhesion is reduced and the anti-adhesion performance is enhanced.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention discloses a high-heat-conducting-efficiency, high-temperature-resistant composite material, a preparation process and its application, and relates to the field of inorganic materials. When preparing the high-heat-conducting-efficiency, high-temperature-resistant composite material, phosphoric acid, aluminum hydroxide, zinc oxide and magnesium oxide are mixed to obtain an inorganic adhesive; magnesium chloride hexahydrate is used to obtain magnesium oxide whiskers by a liquid phase method; silicon dioxide, aluminum oxide, magnesium oxide whiskers and zinc oxide are mixed and ball-milled to obtain a composite ceramic powder; the composite ceramic powder and the inorganic adhesive are mixed and then sprayed on an aluminum substrate to obtain a high-heat-conducting-efficiency, high-temperature-resistant composite material. The high-heat-conducting-efficiency, high-temperature-resistant composite material prepared by the present invention has excellent anti-sticking performance, durability, thermal conductivity and high-temperature resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of inorganic materials, and in particular to a high-heat conduction efficiency high-temperature resistant composite material, a preparation process and an application thereof. Background Art

[0002] Rice is one of the most consumed staple foods in my country. With the rapid development of economy and technology, rice cookers have become the most commonly used appliance for cooking rice in households. Users not only require that the cooked rice is delicious, but also that the food is healthy and safe and the product is durable. As the inner pot of the rice cooker that is in direct contact with food, its safety and reliability are particularly important. The convenience brought by the non-stick coating greatly meets different usage requirements. However, the use of the non-stick coating also brings certain health and safety threats to consumers, namely, problems such as sticking to the pot caused by the peeling of the inner pot coating. Therefore, the present invention prepares a high-temperature resistant composite material with high thermal conductivity efficiency and excellent durability. Summary of the invention

[0003] The purpose of the present invention is to provide a high-heat conduction efficiency high-temperature resistant composite material, a preparation process and an application thereof, so as to solve the problems existing in the prior art.

[0004] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0005] A high-heat-conducting-efficiency, high-temperature-resistant composite material is obtained by mixing composite ceramic powder and inorganic adhesive and then spraying the mixture on an aluminum substrate.

[0006] As an optimization, the inorganic adhesive is obtained by mixing phosphoric acid, aluminum hydroxide, zinc oxide and magnesium oxide;

[0007] As an optimization, the phosphoric acid model is food grade and comes from Shenyang Congke Chemical Co., Ltd.

[0008] As an optimization, the aluminum hydroxide model is food grade and comes from Wuhan Huaxiang Kejie Biotechnology Co., Ltd.

[0009] As an optimization, the zinc oxide model is food grade and comes from Hebei Hanbang Chemical Technology Co., Ltd.

[0010] As an optimization, the magnesium oxide model is food grade and comes from Hebei Meishen Technology Co., Ltd.

[0011] As an optimization, the composite ceramic powder is obtained by mixing and ball-milling silicon dioxide, aluminum oxide, magnesium oxide whiskers and zinc oxide.

[0012] As an optimization, the silicon dioxide model is food grade and comes from Guangzhou Huayu Biotechnology Co., Ltd.

[0013] As an optimization, the alumina comes from Nangong Xindu Metal Materials Technology Co., Ltd.

[0014] As an optimization, the zinc oxide model is food grade and comes from Hebei Hanbang Chemical Technology Co., Ltd.

[0015] As an optimization, the magnesium oxide whiskers are prepared from magnesium chloride hexahydrate by a liquid phase method.

[0016] As an optimization, the magnesium chloride hexahydrate is of food grade and comes from Weifang Hechuang Chemical Co., Ltd.

[0017] A preparation process of a high-heat-conducting-efficiency, high-temperature-resistant composite material comprises the following preparation steps:

[0018] (1) Phosphoric acid and deionized water are mixed in a mass ratio of 1:(10-20), stirred at 20-30° C. and 100-200 rpm for 30-40 min, aluminum hydroxide with a molar amount of 0.2-0.4 times that of phosphoric acid and zinc oxide with a molar amount of 0.1-0.2 times that of phosphoric acid are added, the temperature is raised to 85-95° C. and stirring is continued for 55-65 min, naturally cooled to room temperature, magnesium oxide with a molar amount of 0.07-0.08 times that of phosphoric acid is added, stirred at 45-55° C. and 200-300 rpm for 55-65 min, and allowed to stand for 1-2 h to obtain an inorganic adhesive;

[0019] (2) Mix magnesium chloride hexahydrate and deionized water in a mass ratio of 1:(8.8-8.9), stir at 20-30° C. and 750-850 r / min for 10-20 min, add 0.4-0.6 mol / L sodium carbonate aqueous solution at a rate of 1-3 drops / s, the ratio of the molar amount of sodium carbonate to the molar amount of magnesium chloride in the sodium carbonate aqueous solution is 1:1, continue stirring for 20-30 min, let stand for 23-25 ​​h, filter, wash with deionized water and anhydrous ethanol for 3-5 times respectively, dry at 75-85° C. for 11-13 h, heat to 650-750° C. at a rate of 4-6° C. / min in an alumina crucible, keep warm for 2-4 h, cool naturally to room temperature, grind and sieve 200-300 mesh to obtain magnesium oxide whiskers;

[0020] (3) mixing silica, alumina, magnesium oxide whiskers and zinc oxide in a mass ratio of 1:(0.1-0.2):(0.3-0.4):(0.2-0.3), adding grinding balls with a diameter of 3-5 mm in an amount of 3-5 times the mass of silica and anhydrous ethanol in an amount of 0.8-0.9 times the mass of silica, and milling for 1-3 h using a planetary ball mill at 350-450 r / min, sieving through 200-300 mesh, and drying at 65-75° C. for 11-13 h to obtain a composite ceramic powder;

[0021] (4) The aluminum substrate is preheated to 160-180°C, and the coating liquid is sprayed with a high-pressure spray gun to a thickness of 160-170 μm under the conditions of an inlet temperature of 215-225°C, an outlet temperature of 115-125°C, a nozzle diameter of 0.7-0.9 mm, a spraying distance of 15-25 cm, an atomizing disk speed of 250-350 Hz, and a spraying flow rate of 100-200 mL / min. The substrate is allowed to stand at 1000-1200°C for 3-5 h in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a high-heat conduction efficiency and high-temperature resistant composite material.

[0022] As an optimization, the coating liquid in step (4) is obtained by mixing composite ceramic powder, inorganic adhesive and deionized water in a mass ratio of 1: (0.07-0.08): (0.3-0.4).

[0023] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0024] When preparing the high-heat-conducting-efficiency high-temperature-resistant composite material, the present invention comprises the following steps: mixing phosphoric acid, aluminum hydroxide, zinc oxide and magnesium oxide to obtain an inorganic adhesive; preparing magnesium oxide whiskers from magnesium chloride hexahydrate by a liquid phase method; mixing silicon dioxide, aluminum oxide, magnesium oxide whiskers and zinc oxide and performing ball milling to obtain a composite ceramic powder; and mixing the composite ceramic powder and the inorganic adhesive and spraying the mixture on an aluminum substrate to obtain the high-heat-conducting-efficiency high-temperature-resistant composite material.

[0025] Firstly, phosphoric acid, aluminum hydroxide, zinc oxide and magnesium oxide are mixed to obtain an inorganic adhesive; magnesium chloride hexahydrate is used to obtain magnesium oxide whiskers by a liquid phase method; a diffusion solid solution interface is formed between the inorganic adhesive and the metal substrate during heating and curing, so as to enhance the bonding strength and improve the durability of the high-heat-conducting-efficiency and high-temperature-resistant composite material; magnesium chloride hexahydrate is made into magnesium oxide whiskers by a solution precipitation method, and a uniform dispersion structure is formed in the ceramic coating, so as to increase the density and uniformity of the coating and improve the thermal conductivity and high-temperature resistance of the high-heat-conducting-efficiency and high-temperature-resistant composite material; at the same time, the thermal expansion coefficient of magnesium oxide is close to that of the aluminum substrate, so as to reduce the generation of internal stress, avoid cracking of the coating and improve the durability of the high-heat-conducting-efficiency and high-temperature-resistant composite material.

[0026] Secondly, silicon dioxide, aluminum oxide, magnesium oxide whisker and zinc oxide are mixed and ball-milled to obtain composite ceramic powder; the composite ceramic powder and inorganic adhesive are mixed and sprayed on an aluminum substrate to obtain a high thermal conductivity and high temperature resistant composite material; the aluminum oxide, magnesium oxide whisker and zinc oxide in the composite ceramic powder can improve the thermal conductivity of the ceramic coating, and improve the thermal conductivity and high temperature resistance of the high thermal conductivity and high temperature resistant composite material; at the same time, it can also promote the curing of the inorganic adhesive to form a continuous chain structure or a three-dimensional network structure with high mechanical strength, thereby improving the durability of the high thermal conductivity and high temperature resistant composite material; irregular concave-convex shapes are formed on the coating surface through high-pressure spraying, thereby improving the surface roughness, reducing adhesion, and enhancing the anti-sticking properties of the high thermal conductivity and high temperature resistant composite material. DETAILED DESCRIPTION

[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0028] Example 1

[0029] A preparation process of a high heat conduction efficiency and high temperature resistant composite material, the preparation process of the high heat conduction efficiency and high temperature resistant composite material comprising the following preparation steps:

[0030] (1) Phosphoric acid and deionized water were mixed in a mass ratio of 1:10, stirred at 20° C. and 100 rpm for 40 min, aluminum hydroxide with a molar amount of 0.2 times that of phosphoric acid and zinc oxide with a molar amount of 0.1 times that of phosphoric acid were added, the temperature was raised to 85° C. and stirred for 65 min, the mixture was naturally cooled to room temperature, magnesium oxide with a molar amount of 0.07 times that of phosphoric acid was added, the mixture was stirred at 45° C. and 200 rpm for 65 min, and the mixture was allowed to stand for 2 h to obtain an inorganic adhesive;

[0031] (2) Magnesium chloride hexahydrate and deionized water are mixed in a mass ratio of 1:8.8, stirred at 20°C and 750 r / min for 20 min, 0.6 mol / L sodium carbonate aqueous solution is added at a rate of 1 drop / s, the molar ratio of sodium carbonate to magnesium chloride in the sodium carbonate aqueous solution is 1:1, stirring is continued for 30 min, and the mixture is filtered after standing for 25 h, washed with deionized water and anhydrous ethanol for 3 times respectively, dried at 75°C for 13 h, heated to 750°C at a rate of 4°C / min in an alumina crucible and kept warm for 2 h, cooled naturally to room temperature, ground and sieved through 200 mesh to obtain magnesium oxide whiskers;

[0032] (3) Silica, alumina, magnesium oxide whiskers and zinc oxide were mixed in a mass ratio of 1:0.1:0.3:0.2, and grinding balls with a diameter of 3 mm, which were 3 times the mass of silica, and anhydrous ethanol, which was 0.8 times the mass of silica, were added, and the mixture was ball-milled at 350 r / min for 3 h using a planetary ball mill, sieved with 200 mesh, and dried at 65° C. for 13 h to obtain a composite ceramic powder;

[0033] (4) The aluminum substrate was preheated to 160°C, and the coating liquid was sprayed to a thickness of 160 μm using a high-pressure spray gun under the conditions of an inlet temperature of 215°C, an outlet temperature of 115°C, a nozzle diameter of 0.7 mm, a spraying distance of 15 cm, an atomizing disk speed of 250 Hz, and a spraying flow rate of 100 mL / min. The substrate was allowed to stand at 1000°C for 5 h in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a high-heat conduction efficiency and high-temperature resistant composite material.

[0034] Example 2

[0035] A preparation process of a high heat conduction efficiency and high temperature resistant composite material, the preparation process of the high heat conduction efficiency and high temperature resistant composite material comprising the following preparation steps:

[0036] (1) Phosphoric acid and deionized water were mixed in a mass ratio of 1:15, stirred at 25° C. and 150 rpm for 35 min, aluminum hydroxide with a molar amount of 0.3 times that of phosphoric acid and zinc oxide with a molar amount of 0.15 times that of phosphoric acid were added, the temperature was raised to 90° C. and stirred for 60 min, the mixture was naturally cooled to room temperature, magnesium oxide with a molar amount of 0.075 times that of phosphoric acid was added, the mixture was stirred at 50° C. and 250 rpm for 60 min, and the mixture was allowed to stand for 1.5 h to obtain an inorganic adhesive;

[0037] (2) Mix magnesium chloride hexahydrate and deionized water in a mass ratio of 1:8.85, stir at 25°C and 800 r / min for 15 min, add 0.5 mol / L sodium carbonate aqueous solution at a rate of 2 drops / s, the molar ratio of sodium carbonate to magnesium chloride in the sodium carbonate aqueous solution is 1:1, continue stirring for 25 min, let stand for 24 h and then filter, wash with deionized water and anhydrous ethanol for 4 times respectively, dry at 80°C for 12 h, heat to 700°C in an alumina crucible at a rate of 5°C / min and keep warm for 3 h, cool naturally to room temperature, grind and sieve 250 mesh to obtain magnesium oxide whiskers;

[0038] (3) Silica, alumina, magnesium oxide whiskers and zinc oxide were mixed in a mass ratio of 1:0.15:0.35:0.25, and 4 mm diameter grinding balls 4 times the mass of silica and 0.85 times the mass of anhydrous ethanol were added, and the mixture was ball milled at 400 r / min for 2 h using a planetary ball mill, sieved with 250 mesh, and dried at 70° C. for 12 h to obtain a composite ceramic powder;

[0039] (4) The aluminum substrate was preheated to 170°C, and the coating liquid was sprayed with a high-pressure spray gun to a thickness of 165 μm under the conditions of an inlet temperature of 220°C, an outlet temperature of 120°C, a nozzle diameter of 0.8 mm, a spraying distance of 20 cm, an atomizing disk speed of 300 Hz, and a spraying flow rate of 150 mL / min. The substrate was allowed to stand at 1100°C for 4 h in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a high thermal conductivity and high temperature resistant composite material.

[0040] Example 3

[0041] A preparation process of a high heat conduction efficiency and high temperature resistant composite material, the preparation process of the high heat conduction efficiency and high temperature resistant composite material comprising the following preparation steps:

[0042] (1) Phosphoric acid and deionized water were mixed in a mass ratio of 1:20, stirred at 30° C. and 200 rpm for 30 min, aluminum hydroxide with a molar amount of 0.4 times that of phosphoric acid and zinc oxide with a molar amount of 0.2 times that of phosphoric acid were added, the temperature was raised to 95° C. and stirred for 55 min, the mixture was naturally cooled to room temperature, magnesium oxide with a molar amount of 0.08 times that of phosphoric acid was added, the mixture was stirred at 55° C. and 300 rpm for 55 min, and the mixture was allowed to stand for 1 h to obtain an inorganic adhesive;

[0043] (2) Magnesium chloride hexahydrate and deionized water are mixed in a mass ratio of 1:8.9, stirred at 30°C and 850 r / min for 10 min, 0.4 mol / L sodium carbonate aqueous solution is added at a rate of 3 drops / s, the molar ratio of sodium carbonate to magnesium chloride in the sodium carbonate aqueous solution is 1:1, stirring is continued for 20 min, and the mixture is filtered after standing for 23 h, washed with deionized water and anhydrous ethanol for 5 times respectively, dried at 85°C for 11 h, heated to 650°C at a rate of 6°C / min in an alumina crucible and kept warm for 4 h, cooled naturally to room temperature, ground and sieved through 300 mesh to obtain magnesium oxide whiskers;

[0044] (3) Silica, alumina, magnesium oxide whiskers and zinc oxide were mixed in a mass ratio of 1:0.2:0.4:0.3, and grinding balls with a diameter of 5 mm and a mass of 5 times that of silica and anhydrous ethanol with a mass of 0.9 times that of silica were added, and the mixture was ball-milled at 450 r / min for 1 h using a planetary ball mill, sieved through 300 mesh, and dried at 75° C. for 11 h to obtain a composite ceramic powder;

[0045] (4) The aluminum substrate was preheated to 180°C, and the coating liquid was sprayed to a thickness of 170 μm using a high-pressure spray gun under the conditions of an inlet temperature of 225°C, an outlet temperature of 125°C, a nozzle diameter of 0.9 mm, a spraying distance of 25 cm, an atomizing disk speed of 350 Hz, and a spraying flow rate of 200 mL / min. The substrate was allowed to stand at 1200°C for 3 h in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a high-heat conduction efficiency and high-temperature resistant composite material.

[0046] Comparative Example 1

[0047] A preparation process of a high heat conduction efficiency and high temperature resistant composite material, the preparation process of the high heat conduction efficiency and high temperature resistant composite material comprising the following preparation steps:

[0048] (1) Magnesium chloride hexahydrate and deionized water are mixed in a mass ratio of 1:8.85, stirred at 25°C and 800 r / min for 15 min, 0.5 mol / L sodium carbonate aqueous solution is added at a rate of 2 drops / s, the molar ratio of sodium carbonate to magnesium chloride in the sodium carbonate aqueous solution is 1:1, stirring is continued for 25 min, and the mixture is filtered after standing for 24 h, washed with deionized water and anhydrous ethanol for 4 times respectively, dried at 80°C for 12 h, heated to 700°C at a rate of 5°C / min in an alumina crucible and kept warm for 3 h, cooled naturally to room temperature, ground and sieved through 250 mesh to obtain magnesium oxide whiskers;

[0049] (2) Silica, alumina, magnesium oxide whiskers and zinc oxide were mixed in a mass ratio of 1:0.15:0.35:0.25, and grinding balls with a diameter of 4 mm, which were 4 times the mass of silica, and anhydrous ethanol, which was 0.85 times the mass of silica, were added, and the mixture was ball-milled at 400 r / min for 2 h using a planetary ball mill, sieved with 250 mesh, and dried at 70° C. for 12 h to obtain a composite ceramic powder;

[0050] (3) The aluminum substrate was preheated to 170°C, and the coating liquid was sprayed to a thickness of 165 μm using a high-pressure spray gun under the conditions of an inlet temperature of 220°C, an outlet temperature of 120°C, a nozzle diameter of 0.8 mm, a spraying distance of 20 cm, an atomizing disk speed of 300 Hz, and a spraying flow rate of 150 mL / min. The substrate was allowed to stand at 1100°C for 4 h in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a high-heat conduction efficiency and high-temperature resistant composite material.

[0051] Comparative Example 2

[0052] A preparation process of a high heat conduction efficiency and high temperature resistant composite material, the preparation process of the high heat conduction efficiency and high temperature resistant composite material comprising the following preparation steps:

[0053] (1) Phosphoric acid and deionized water were mixed in a mass ratio of 1:15, stirred at 25° C. and 150 rpm for 35 min, aluminum hydroxide with a molar amount of 0.3 times that of phosphoric acid and zinc oxide with a molar amount of 0.15 times that of phosphoric acid were added, the temperature was raised to 90° C. and stirred for 60 min, the mixture was naturally cooled to room temperature, magnesium oxide with a molar amount of 0.075 times that of phosphoric acid was added, the mixture was stirred at 50° C. and 250 rpm for 60 min, and the mixture was allowed to stand for 1.5 h to obtain an inorganic adhesive;

[0054] (2) Silica, alumina and zinc oxide were mixed in a mass ratio of 1:0.15:0.25, and grinding balls with a diameter of 4 mm, which were 4 times the mass of silica, and anhydrous ethanol, which was 0.85 times the mass of silica, were added, and the mixture was ball-milled at 400 r / min for 2 h using a planetary ball mill, sieved with 250 mesh, and dried at 70° C. for 12 h to obtain a composite ceramic powder;

[0055] (3) The aluminum substrate was preheated to 170°C, and the coating liquid was sprayed to a thickness of 165 μm using a high-pressure spray gun under the conditions of an inlet temperature of 220°C, an outlet temperature of 120°C, a nozzle diameter of 0.8 mm, a spraying distance of 20 cm, an atomizing disk speed of 300 Hz, and a spraying flow rate of 150 mL / min. The substrate was allowed to stand at 1100°C for 4 h in a nitrogen atmosphere, and naturally cooled to room temperature to obtain a high-heat conduction efficiency and high-temperature resistant composite material.

[0056] Comparative Example 3

[0057] A preparation process of a high heat conduction efficiency and high temperature resistant composite material, the preparation process of the high heat conduction efficiency and high temperature resistant composite material comprising the following preparation steps:

[0058] (1) Phosphoric acid and deionized water were mixed in a mass ratio of 1:15, stirred at 25° C. and 150 rpm for 35 min, aluminum hydroxide with a molar amount of 0.3 times that of phosphoric acid and zinc oxide with a molar amount of 0.15 times that of phosphoric acid were added, the temperature was raised to 90° C. and stirred for 60 min, the mixture was naturally cooled to room temperature, magnesium oxide with a molar amount of 0.075 times that of phosphoric acid was added, the mixture was stirred at 50° C. and 250 rpm for 60 min, and the mixture was allowed to stand for 1.5 h to obtain an inorganic adhesive;

[0059] (2) Mix magnesium chloride hexahydrate and deionized water in a mass ratio of 1:8.85, stir at 25°C and 800 r / min for 15 min, add 0.5 mol / L sodium carbonate aqueous solution at a rate of 2 drops / s, the molar ratio of sodium carbonate to magnesium chloride in the sodium carbonate aqueous solution is 1:1, continue stirring for 25 min, let stand for 24 h and then filter, wash with deionized water and anhydrous ethanol for 4 times respectively, dry at 80°C for 12 h, heat to 700°C in an alumina crucible at a rate of 5°C / min and keep warm for 3 h, cool naturally to room temperature, grind and sieve 250 mesh to obtain magnesium oxide whiskers;

[0060] (3) Silica, alumina, magnesium oxide whiskers and zinc oxide were mixed in a mass ratio of 1:0.15:0.35:0.25, and 4 mm diameter grinding balls 4 times the mass of silica and 0.85 times the mass of anhydrous ethanol were added, and the mixture was ball milled at 400 r / min for 2 h using a planetary ball mill, sieved with 250 mesh, and dried at 70° C. for 12 h to obtain a composite ceramic powder;

[0061] (4) A layer of coating liquid is applied on the surface of the aluminum substrate with a brush, and the coating is dried at 25°C for 12 hours. The coating is applied again and dried for 12 hours. The coating is heated to 1100°C at a rate of 5°C / min in a nitrogen atmosphere and allowed to stand for 4 hours. The coating is naturally cooled to room temperature to obtain a high-heat-conducting-efficiency, high-temperature-resistant composite material.

[0062] Test Case

[0063] 1. Anti-stick performance

[0064] Test method: The high heat conduction efficiency and high temperature resistant composite materials obtained in each embodiment and the comparative example were respectively cooked and cleaned according to GB / T32095, and the cooking was repeated 10 times to observe the stickiness.

[0065] 2. Durability

[0066] Test method: Weigh the initial mass m0 of the high thermal conductivity and high temperature resistant composite materials obtained in each embodiment and the comparative example respectively, treat them for 8 hours using a controllable friction and wear testing machine under the conditions of a load of 300g Si3N4 small balls with a diameter of 6mm and a rotation speed of 800r / min, weigh m1 again, calculate the wear amount = m1-m0, and judge the wear resistance.

[0067] 3. Thermal conductivity

[0068] Test method: The thermal conductivity of the high heat conduction efficiency and high temperature resistant composite materials obtained in each embodiment and the comparative example is tested according to GB / T39862.

[0069] 4. High temperature resistance

[0070] Test method: The high thermal conductivity and high temperature resistant composite materials obtained in each embodiment and the comparative example were kept at 250°C for 10 minutes according to GB / T32095, then placed in deionized water, cooled for 2 minutes, taken out and wiped dry, and the surface cracks were observed to determine the high temperature resistance.

[0071] Table 1 below shows the analysis results of the anti-sticking performance, durability, thermal conductivity and high temperature resistance of the high heat conduction efficiency and high temperature resistant composite materials of Examples 1 to 3 of the present invention and Comparative Examples 1 to 3.

[0072] Table 1

[0073] Sticky situation <![CDATA[Wear amount mg / cm 2 > Thermal conductivity W / m·K Surface cracks Example 1 Non-stick 9 13.1 No cracks Example 2 Non-stick 8 13.4 No cracks Example 3 Non-stick 9 12.9 No cracks Comparative Example 1 Non-stick 69 10.8 No cracks Comparative Example 2 Non-stick 53 3.4 Micro cracks Comparative Example 3 Slightly sticky 17 11.9 No cracks

[0074] From the comparison of the experimental data of Examples 1 to 3 and Comparative Examples 1 to 3 in Table 1, it can be found that the high heat conduction efficiency and high temperature resistant composite material prepared by the present invention has good anti-sticking performance, durability, thermal conductivity and high temperature resistance.

[0075] By comparison, the wear amount of Examples 1, 2, and 3 is lower than that of Comparative Example 1, which indicates that a diffusion solid solution interface is formed between the inorganic adhesive and the metal substrate when heated and cured, thereby enhancing the bonding strength and improving the durability of the high thermal conductivity and high temperature resistant composite material; at the same time, the aluminum oxide, magnesium oxide whiskers and zinc oxide in the composite ceramic powder can also promote the curing of the inorganic adhesive to form a continuous chain structure or a three-dimensional network structure with high mechanical strength, thereby further improving the durability of the high thermal conductivity and high temperature resistant composite material.

[0076] By comparison, Examples 1, 2, and 3 have lower wear, higher thermal conductivity, and fine cracks than Comparative Example 2, indicating that magnesium chloride hexahydrate is made into magnesium oxide whiskers by a solution precipitation method, forming a uniform dispersed structure in the ceramic coating, increasing the density and uniformity of the coating, and improving the thermal conductivity and high temperature resistance of the high thermal conductivity efficiency and high temperature resistant composite material; at the same time, the thermal expansion coefficient of magnesium oxide is close to that of the aluminum substrate, which can reduce the generation of internal stress, avoid cracking of the coating, and improve the durability of the high thermal conductivity efficiency and high temperature resistant composite material.

[0077] By comparison, the adhesion of Examples 1, 2, and 3 is better than that of Comparative Example 3, which indicates that irregular concave-convex shapes are formed on the coating surface by high-pressure spraying, which improves the surface roughness, reduces adhesion, and enhances the anti-sticking performance of the high heat conduction efficiency and high temperature resistant composite material.

[0078] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A high-heat-conducting-efficiency, high-temperature-resistant composite material, characterized in that: The high heat conduction efficiency high temperature resistant composite material is obtained by spraying a coating liquid on a preheated aluminum substrate, and then performing a heat treatment at 1000-1200°C in a nitrogen atmosphere; The coating liquid is obtained by mixing composite ceramic powder, inorganic adhesive and deionized water in a mass ratio of 1:(0.07-0.08):(0.3-0.4); The inorganic adhesive is obtained by mixing phosphoric acid, aluminum hydroxide, zinc oxide and magnesium oxide; The composite ceramic powder is obtained by mixing and ball-milling silicon dioxide, aluminum oxide, magnesium oxide whiskers and zinc oxide; The magnesium oxide whiskers are prepared from magnesium chloride hexahydrate by a liquid phase method; The preparation steps of the inorganic adhesive are as follows: phosphoric acid and deionized water are mixed in a mass ratio of 1: (10-20), stirred at 20-30° C. and 100-200 rpm for 30-40 min, aluminum hydroxide with a molar amount of 0.2-0.4 times that of phosphoric acid and zinc oxide with a molar amount of 0.1-0.2 times that of phosphoric acid are added, the temperature is raised to 85-95° C. and the stirring is continued for 55-65 min, the mixture is naturally cooled to room temperature, magnesium oxide with a molar amount of 0.07-0.08 times that of phosphoric acid is added, the mixture is stirred at 45-55° C. and 200-300 rpm for 55-65 min, and the mixture is allowed to stand for 1-2 h to obtain the inorganic adhesive.

2. A process for preparing the high-heat-conducting-efficiency high-temperature-resistant composite material according to claim 1, characterized in that: The method comprises the following preparation steps: (1) Phosphoric acid and deionized water are mixed in a mass ratio of 1:(10-20), stirred at 20-30°C and 100-200 rpm for 30-40 min, aluminum hydroxide with a molar weight of 0.2-0.4 times that of phosphoric acid and zinc oxide with a molar weight of 0.1-0.2 times that of phosphoric acid are added, the temperature is raised to 85-95°C and stirring is continued for 55-65 min, naturally cooled to room temperature, magnesium oxide with a molar weight of 0.07-0.08 times that of phosphoric acid is added, stirred at 45-55°C and 200-300 rpm for 55-65 min, and allowed to stand for 1-2 h to obtain an inorganic adhesive; (2) Mix magnesium chloride hexahydrate and deionized water in a mass ratio of 1:(8.8~8.9), stir at 20~30°C and 750~850r / min for 10~20min, add sodium carbonate aqueous solution at a rate of 1~3 drops / s, the ratio of the molar amount of sodium carbonate to the molar amount of magnesium chloride in the sodium carbonate aqueous solution is 1:1, continue stirring for 20~30min, let stand for 23~25h and then filter, wash with deionized water and anhydrous ethanol for 3~5 times respectively, dry at 75~85°C for 11~13h, heat to 650~750°C at a rate of 4~6°C / min in an alumina crucible and keep warm for 2~4h, cool naturally to room temperature, grind and sieve 200~300 mesh to obtain magnesium oxide whiskers; (3) Mix silica, alumina, magnesium oxide whiskers and zinc oxide in proportion, add grinding balls with a diameter of 3 to 5 mm that are 3 to 5 times the mass of silica and anhydrous ethanol that is 0.8 to 0.9 times the mass of silica, and use a planetary ball mill to mill for 1 to 3 hours at 350 to 450 r / min. Sieve through 200 to 300 meshes, and dry at 65 to 75°C for 11 to 13 hours to obtain a composite ceramic powder. (4) Preheat the aluminum substrate to 160-180°C, spray the coating liquid to a thickness of 160-170 μm using a high-pressure spray gun under certain spraying conditions, let it stand at 1000-1200°C for 3-5 hours in a nitrogen atmosphere, and naturally cool to room temperature to obtain a high-temperature resistant composite material with high thermal conductivity efficiency.

3. The preparation process of a high heat conduction efficiency high temperature resistant composite material according to claim 2, characterized in that: The sodium carbonate aqueous solution in step (2) is 0.4-0.6 mol / L.

4. The preparation process of a high heat conduction efficiency high temperature resistant composite material according to claim 2, characterized in that: In step (3), the silicon dioxide, aluminum oxide, magnesium oxide whisker and zinc oxide are mixed in a mass ratio of 1:(0.1-0.2):(0.3-0.4):(0.2-0.3).

5. The preparation process of a high heat conduction efficiency high temperature resistant composite material according to claim 2, characterized in that: The certain spraying conditions in step (4) are: inlet temperature 215~225°C, outlet temperature 115~125°C, nozzle diameter 0.7~0.9mm, spraying distance 15~25cm, atomizing disk speed 250~350Hz, and spraying flow rate 100~200mL / min.

6. Use of the high heat conduction efficiency and high temperature resistant composite material according to claim 1 in a stainless steel inner pot of an electric rice cooker.

Citation Information

Patent Citations

  • Preparation method of high-temperature chlorine corrosion resistant coating with attapulgite clay as base material for incinerator

    CN114774833A

  • High-temperature-resistant anti-corrosion wear-resistant composite coating and preparation method thereof

    CN116478564A